Framing elite sport sponsorships in Finland: Strategic perspectives and dimensions of legitimacy - Lepomäki, Jutta (2025)
Lepomäki, J. 2025. Framing elite sport sponsorships in Finland: Strategic perspectives and dimensions of legitimacy. Faculty of Sport and Health Sciences, University of Jyväskylä. Master’s thesis, Responsible Management and Business of Sport. 90 pages, 2 appendices.